Opioid System Modulates the Immune Function: A Review - Liang, Xuan (Transl Perioper Pain Med, 2016)
Opioid receptors and their ligands produce powerful analgesia that is effective in perioperative period and chronic pain managements accompanied with various side effects including respiratory depression, constipation and addiction etc. Opioids can also interfere with the immune system, not only participating in the function of the immune cells, but also modulating innate and acquired immune responses. The traditional notion of opioids is immunosuppressive. Recent studies indicate that the role of opioid receptors on immune function is complicated, working through various different mechanisms. Different opioids or opioids administrations show various effects on the immune system: immunosuppressive, immunostimulatory, or dual effect. It is important to elucidate the relationship between opioids and immune function, since immune system plays critical role in various physiological and pathophysiological processes, including the inflammation, tumor growth and metastasis, drug abuse, and so on. This review article tends to have an overview of the recent work and perspectives on opioids and the immune function.